Determinants of demand for prepared meals in Greece - Λαζαρίδης Παναγιώτης (SPOUDAI Journal of Economics and Business, 2001)
In this paper the factors affecting demand for prepared meals by Greek households are investigated assuming a two-step decision process. A selectivity model is employed to derive the necessary elasticities using information at household level gathered by the National Statistical Service of Greece. Household income, size and age composition, age, occupation and education of the person responsible for food purchases as well as area population, were all important determinants in one or both stages of the decision process. According to the results this food category behaves mostly as a luxury and it is associated more to the available free time of the family adults and less to a model that stresses the opportunity cost of time of the working family members. JEL Classification: Q11, C24